Prototype System of Car Rat Detection Radar Using ESP8266 Microcontroller Based on Internet of Things - Riyad Ari, Muhamad Riyad Ariwibowo; Juju Juhaeriyah; Muhammad Rizal Mahardika; Ahmad Syahruli, (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
The advancement of technology in sensing and object detection systems has been widely applied in various fields. In object distance monitoring systems, radar systems are designed to address blind spots and measure approaching distances dynamically and accurately using ultrasonic waves. One utilization of object detection sensors is the ultrasonic HC-SR04 sensor. The ultrasonic sensor test aims to detect the accuracy of objects against rats that may appear in parked cars. This radar system implementation uses a buzzer and LED for sound alerts when a rat is approaching. This research uses the ESP8266 microcontroller as the control, to send the distance information received by the sensor via the Blynk application, and the buzzer gives a loud sound when the object approaches. This radar system can detect a maximum distance of 400 cm with an accuracy of 100 cm and a minimum distance of 2 cm at a 180˚ angle. Thus, the ESP8266-based radar system can provide accuracy in detecting the distance of objects detected by the ultrasonic sensor.